The effect of different desalting methods on the quality of injected brine and pickle salted frozen cod (Gadus morhua) - Dargentolle, Cécile; Sveinsdóttir, Hildur Inga; Arason, Sigurjón; Sveinsdóttir, Kolbrún (Zenodo, 2024)
The demand for ready-to-use desalted or rehydrated products have increased, creating a need for large-scale industrial production of desalted products. In order to adjust to market requirements, the desalting phase must therefore be included in industrial operations. The effects of three different desalting methods (control, movement, flow) for both brine and pickle salted cod on quality parameters of the resulting desalted samples have been studied (Mohammed Raheem Waheed Almozani, 2021) on desalting yield, cooking yield, colour, texture, salt content, water content, and desalting time. The purpose of this report was to evaluate if freezing and frozen storage of six months at -25°C of the desalted cod had an influence on its properties as compared to the unfrozen desalted samples. Freezing had an impact on the properties of both on the desalted brine salted and pickle salted samples regarding the texture changes, as well as the salt repartition in the samples. Impact on the yellow colour was also noticeable, mainly on the pickle salted samples for the movement and flow groups. Overall, frozen storage improved attributes in the case of desalted pickle salted samples as compared to unfrozen, while the impact of frozen storage of the desalted brine salted samples was more negative with a huge loss of hardness independently of the desalting method as well as an increase in the yellowness of the samples. _____ Aukin eftirspurn eftir tilbúnum útvötnuðum afurðum hefur gert það að verkum að nú er þörf fyrir framleiðslu útvatnaðar afurða á iðnaðarskala. Til að mæta kröfum markaðarins þarf útvötnun að vera hluti framleiðsluferlisins. Áhrif þriggja mismunandi aðferða (viðmið, hreyfing, flæði) til útvötnunar fullverkaðra saltfiskafurða (með pæklun eða pækilsöltun) á gæðaþætti útvatnaðra afurða hafa verið rannsökuð hvað varðar nýtingu eftir útvötnun, suðunýtingu, lit, áferð, salt innihald, vatnsinnihald og útvötnunartíma (Mohammed Raheem Waheed Almozani, 2021). Tilgangur þessarar rannsóknar var að meta áhrif frystingar og ...